Pengelolaan Lahan Tailing Timah di Pulau Bangka: Penelitian yang Telah Dilakukan dan Prospek ke Depan - Inonu, Ismed (Universitas Bangka Belitung, 2008)
Tin mining activities have been taking place in Bangka Island since early years ago. Impacts of mining operations are decrease in soil physical and chemical properties, changes in land topography, losses of natural vegetations, and diminishing wildlife habitat. Ex-tin mining land is widely covered by the spread of tailings. Tin tailings have poor physical and chemical characteristic, soil conditions and unfavourable micro-climate. To reuse ex-tin mining land, especially tailing land, reclaimation and rehabilitation programs be required. Applications of various ameliorants and technology has been tested to obtain satisfactory results, particularly the addition of organic matters. A number of specific local plant species including industrial forest tree such as acacia, and some fruit tree species have been selected for ex-tin mining land revegetation. In future, research in revegetation technique will be focused on usage of locally potential organic matter for tailing amendment and selection of some revegetation species which are more useful to increase social economic community. Keywords : tin mining, tailing, revegetation, organic matter